Photoperiod-induced mixotrophic metabolism in Chlorella vulgaris for high biomass and lipid to biodiesel productions using municipal wastewater medium - Leong, W.H. (Elsevier Ltd, 2022)
The performances of autotrophic and heterotrophic metabolisms in Chlorella vulgaris were assessed from various photoperiod regimes for the sustainable microalgal biodiesel production. Accordingly, the cellular biomass growth and lipid content in relation to the organic nutrient removals from municipal wastewater medium were evaluated from the various light/dark photoperiod cycles amidst mixotrophic metabolism. The mixotrophic treatment had been proven effective in producing high microalgal biomass and lipid while alternating its autotrophic and heterotrophic metabolisms. Thus, exploiting the optimum cellular biosynthesis pathways in inducing both biomass growth and lipid accumulation. Amidst mixotrophy, prolonging light condition would favour biomass growth, whilst extending dark condition had elevated cell lipid content. Accordingly, the 16:8 (light:dark) hours/cycle photoperiod was found adequate in yielding high biomass and lipid productions (0.89 and 0.16 g/L, respectively), while achieving near complete removal (>94) of chemical oxygen demand and ammonium-nitrogen from municipal wastewater. The dominant FAME constituents of C16 and C18 comprised of 90.65-100 of total FAME with the high unsaturation degree could proffer an excellent quality of microalgal biodiesel with low pour point, suitable for application in cold climate regions. Â© 2021 Elsevier Ltd